2018
DOI: 10.1021/acsami.7b16407
|View full text |Cite
|
Sign up to set email alerts
|

Dominating Role of Aligned MoS2/Ni3S2 Nanoarrays Supported on Three-Dimensional Ni Foam with Hydrophilic Interface for Highly Enhanced Hydrogen Evolution Reaction

Abstract: When using water splitting to achieve sustainable hydrogen production, low-cost, stable, and naturally abundant electrocatalysts are required to replace Pt-based ones for the hydrogen evolution reaction (HER). Herein, for the first time, a novel nanostructure with one-dimensional (1D) MoS/NiS nanoarrays directly grow on a three-dimensional (3D) Ni foam is developed for this purpose, showing excellent catalytic activity and stability. The as-prepared 3D MoS/NiS/Ni composite has an onset overpotential as low as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(86 citation statements)
references
References 52 publications
4
82
0
Order By: Relevance
“…Note that NF, Pt/C-NF, Ni 7 S 6 & Ni 3 S 2 -NF and MoS 2 /Ni 3 S 2 NW-NF show CAs of 137°, 126°, 98°a nd 0°, respectively. It has been reported that surface energy of MoS 2 increases with increasing number of layers and low crystalline can further increase the wettability [35][36][37]. Therefore, the super hydrophilicity of MoS 2 /Ni 3 S 2 NW-NF can be due to the multilayer and low-crystallinity structure of the outer MoS 2 nanosheets in MoS 2 /Ni 3 S 2 heterostructure, which have been proved by TEM and XRD results shown above.…”
Section: Resultsmentioning
confidence: 63%
“…Note that NF, Pt/C-NF, Ni 7 S 6 & Ni 3 S 2 -NF and MoS 2 /Ni 3 S 2 NW-NF show CAs of 137°, 126°, 98°a nd 0°, respectively. It has been reported that surface energy of MoS 2 increases with increasing number of layers and low crystalline can further increase the wettability [35][36][37]. Therefore, the super hydrophilicity of MoS 2 /Ni 3 S 2 NW-NF can be due to the multilayer and low-crystallinity structure of the outer MoS 2 nanosheets in MoS 2 /Ni 3 S 2 heterostructure, which have been proved by TEM and XRD results shown above.…”
Section: Resultsmentioning
confidence: 63%
“…The transformation of Cu(OH) 2 into Cu 2 S was verified in terms of these intense diffraction peaks at 24.0°, 27.1°, 28.2°, 29.3°, 33.0°, 33.7°, 35.6°, 37.6°, 38.8°, 46.1°,and 48.6°, corresponding to the respective (122), (032), (222), (132), (240), (012), (402), (034), (422), (630) and (106) planes of Cu 2 S (JCPDS No.83‐1462) . Compared to the diffraction peaks of Cu 2 S/CF, the bulges of Cu 2 S/MoS 2 /CF at 14.1° and 39.2° correspond to the (002) and (100) lattice planes of MoS 2 (JCPDS NO.75‐1539) . These results suggested that Cu 2 S and MoS 2 were successfully fabricated in light of the anticipated reaction.…”
Section: Resultsmentioning
confidence: 90%
“…[19b] Compared to the diffraction peaks of Cu 2 S/CF, the bulges of Cu 2 S/MoS 2 /CF at 14.1°and 39.2°c orrespond to the (002) and (100) NO.75-1539). [20] These results suggested that Cu 2 S and MoS 2 were successfully fabricated in light of the anticipated reaction.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…8 Efforts to mitigate CO poisoning of Pt nanoparticles can be made through the addition of some metals, such as Ru, [9][10][11] Sn, 12 Ni. 13 Among them, nickel-based nano-materials not only have been proved to show electrocatalytic activity toward alcohols oxidation but also have been used in the hydrogen evolution reaction, 14,15 the hydrolytic dehydrogenation, 16 the electrolytic hydrogen generation, and the hydrogen peroxide reduction reaction, 17,18 as non-noble metal catalysts.…”
Section: Introductionmentioning
confidence: 99%